HIV Infection, Pulmonary Tuberculosis, and COPD in Rural Uganda: A Cross-Sectional Study - North, Crystal M.; Allen, Joseph G.; Okello, Samson; Sentongo, Ruth; Kakuhikire, Bernard; Ryan, Edward T.; Tsai, Alexander C.; Christiani, David C.; Siedner, Mark J. (Lung, 2018)
Purpose HIV is associated with chronic obstructive pulmonary disease (COPD) in high resource settings. Similar relationships are less understood in low resource settings. We aimed to estimate the association between HIV infection, tuberculosis, and COPD in rural Uganda. Methods The Uganda Non-communicable Diseases and Aging Cohort study observes people 40 years and older living with HIV (PLWH) on antiretroviral therapy, and population-based HIV-uninfected controls in rural Uganda. Participants completed respiratory questionnaires and post-bronchodilator spirometry. Results Among 269 participants with spirometry, median age was 52 (IQR 48–55), 48% (n = 130) were ever-smokers, and few (3%, n = 9) reported a history of COPD or asthma. All participants with prior tuberculosis (7%, n = 18) were PLWH. Among 143 (53%) PLWH, median CD4 count was 477 cells/mm3 and 131 (92%) were virologically suppressed. FEV1 was lower among older individuals (− 0.5%pred/year, 95% CI 0.2–0.8, p < 0.01) and those with a history of tuberculosis (− 14.4%pred, 95% CI − 23.5 to − 5.3, p < 0.01). COPD was diagnosed in 9 (4%) participants, eight of whom (89%) were PLWH, six of whom (67%) had a history of tuberculosis, and all of whom (100%) were men. Among 287 participants with complete symptom questionnaires, respiratory symptoms were more likely among women (AOR 3.9, 95% CI 2.0–7.7, p < 0.001) and those in homes cooking with charcoal (AOR 3.2, 95% CI 1.4–7.4, p = 0.008). Conclusion In rural Uganda, COPD may be more prevalent among PLWH, men, and those with prior tuberculosis. Future research is needed to confirm these findings and evaluate their broader impacts on health.
Keywords: Spirometry; Africa; Lung function; AIDS; Tuberculosis